PENGARUH PERMAINAN BINGO ANGKA TERHADAP KEMAMPUAN MENGENAL LAMBANG BILANGAN PADA ANAK USIA 4-5 TAHUN DI TK NURUL HUDA KECAMATAN BUKIT RAYA KOTA PEKANBARU - Indri Cahya Dita; Daviq Chairilsyah; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on the initial description obtained from observations at the research location in TK Nurul Huda, Bukit Raya Sub-District, several problems were found: some children were still confused if the child mentioned number 4 but the number 5 was indicated, when the teacher wrote 1-10 on the board and ask the child to answer and point to the number 7 on the board, only a few children are able to answer and point to the number, when the child is asked by the teacher to connect the symbol according to the number symbol on the child worksheet, there are still many children who are wrong in connecting it.This study aims to determine the effect of the game Bingo Numbers on the ability to recognize the symbol of numbers of children aged 4-5 years in TK Nurul Huda, Bukit Raya City, Pekanbaru. This study used an experimental method with the design of the pretest posttest control research group design. The population in this study were children aged 4-5 years totaling 40 children and the sample used was 40 children divided into two classes, the experimental class and the control class. The data collection techniques used are observation. Data analysis techniques use the t-test. The results of this research hypothesis test obtained t = 18,689 with sig. (2-tailed) = 0,000 <0,05 which means that there is an influence of the ability to recognize a very significant number symbol after using the Bingo Numbers game during the learning process. Effect of Bingo games Numbers on the ability to recognize the symbol of the number of children aged 4-5 years in TK Nurul Huda, Bukit Raya City, Pekanbaru, amounting to 45% included in the medium category.Keywords: Number Symbol, Bingo Number